Cost-effectiveness analysis of first-line versus second-line use of CDK4/6 inhibitors combined with endocrine therapy in advanced HR+/HER2- breast cancer in China: based on the SONIA trial - Jin, Xiaohu; Li, Zhifeng (Frontiers in Pharmacology, 2025)
BackgroundThe optimal sequencing of CDK4/6 inhibitors combined with endocrine therapy for advanced hormone receptor-positive, HER2-negative (HR+/HER2-) breast cancer remains uncertain, particularly in resource-limited settings such as China. This study evaluated the cost-effectiveness of first-line versus second-line CDK4/6 inhibitor use based on the SONIA trial.MethodsA partitioned survival model was developed to compare costs and effectiveness of first-line (CDK4/6i-first) versus second-line (CDK4/6i-second) CDK4/6 inhibitor strategies among Chinese women with advanced HR+/HER2- breast cancer. Model inputs were derived from the SONIA trial and Chinese healthcare data. Outcomes included total costs, life years (LYs), quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs). Both deterministic and probabilistic sensitivity analyses were performed. Scenario analyses incorporated generic drug pricing.ResultsThe base-case analysis showed that the CDK4/6i-first strategy yielded 3.07 QALYs at a lifetime cost of CNY 372420.21, compared to 2.86 QALYs and CNY 366445.93 for the CDK4/6i-second strategy. The ICER for first-line CDK4/6 inhibitor use was CNY 28126.33 per QALY, well below the willingness-to-pay (WTP) threshold of CNY 287,247/QALY. Scenario analysis with generics showed an ICER of CNY 198439.62 per QALY. Sensitivity analyses confirmed the robustness of these results.ConclusionThis study supports the early use of CDK4/6 inhibitors combined with endocrine therapy as a cost-effective strategy for advanced HR+/HER2- breast cancer in China. Continued real-world monitoring is needed to adapt to changes in drug pricing and clinical practice.